Genetic polymorphisms in the glutamate-rich protein of Plasmodium falciparum field isolates from a malaria-endemic area of Brazil - Riccio, Lilian Rose Pratt (2013)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisas em Malária. Rio de Janeiro, RJ, Brasil.